The Problem of Holistic Education in Theory and Practice of New Pedagogy - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 2005)
The article analyses holistic education in historical aspect. Author gives the development of principle integration in the antiquity, classical pedagogy. The great importance is attaching to holistic education in theory and practice of new pedagogy of beginning of XX ct. The views of various scientists and practical educators (J. Dewey, T. Hopkins, F. Forster, W. James, G. Kerschensteiner, F. Parker, P. Search, W. Wirt, C. Washburne and others) to integrated education are presented. The author underlines that integrated education the mostly associated with problem solving method, that was theoretically reasoned by J. Dewey. The article notices that Lithuania educators also were interested in integrated education and employed it in their practice (M. Mačernis, J. Laužikas, J. Vabalas-Gudaitis, A. Vireliūnas, V: Augustauskas, A. Liaugminas and other).
Keywords: history of education; holistic education; integrated education; new pedagogy; correlation